(untitled) (Asian Journal of Medical and Biological Research, 2017)
A study was conducted to determine the efficacy of three most commonly used growth promoters from different pharmaceutical companies on growth performance of hybrid walking catfish (Clarias batrachus × Clarias gariepinus). The experiment was done in the wet laboratory of the Department of Aquaculture, BAU, Mymensingh, with a total of 10 aquaria and 160 fish having mean initial weight of 6.3 ± 0.48 g. The three growth promoters, Charger gel from Fishtech (BD) Ltd., Growth gel from Advance Agrotech (BD) Ltd. and Hepaprotect-aqua from Renata Animal health Ltd., were used in separate nine (9) aquaria at recommended, lower dose and higher dose respectively. One aquarium was used as control (diet without any growth promoter). The fish were fed with paragon nursery floating feed at 20% of body weight in each aquarium for 28 days. Doses of Charger gel were given as 80, 60 and 100 mg/20 g feed/day, that of Growth gel, 0.14, 0.12 and 0.16 ml/20 g feed/day and of Hepaprotect-aqua, 30, 15 and 50 mg/20 g feed/day. Re-circulatory system was used throughout the experimental period. By applying recommended, lower and higher dose of Charger gel, mean final weights were found as 23.0, 21.9 and 35.9 g; average daily weight gain as 0.60, 0.56 and 1.06 g and specific growth rate (SGR) as 2.01, 1.93 and 2.70% respectively. For Growth gel, mean final weights were found as 22.8, 17.3 and 31.1 g; average daily weight gain as 0.59, 0.39 and 0.88 g and SGR as 1.99, 1.57 and 2.48 % respectively. For Hepaprotect-aqua, mean final weights were found as 24.2, 17.5 and 28.2 g; average daily weight gain as 0.64, 0.40 and 0.78 g and SGR as 2.09, 1.58 and 2.32% respectively. In all the cases survival rates were 100%. All the three growth promoters showed better results at their higher doses in comparison to their results in lower and recommended doses. However, in average Charger gel showed the best result than the other two growth promoters. This information on the efficacy study of growth promoters needs to be disseminated to the farmers for improved fish production. Asian J. Med. Biol. Res. March 2017, 3(1): 103-108